Use of probiotics in preventing and treating excess weight and obesity. A systematic review - Belén Torres; María C. Sánchez; Leire Virto; Arancha Llama‐Palacios; María J. Ciudad; Luis Collado (Wiley, 2024)
Abstract Background The prevalence of excess weight and obesity is increasing in an extremely concerning manner worldwide, with highly diverse therapies for current treatment. This review evaluated the scientific evidence of the past 10 years on the use of probiotics in treating excess weight and obesity in the absence of dieting. Materials A systematic review was conducted by searching for clinical trials on humans published in English in the PubMed, Scopus and Cochrane Central databases, using the combination of keywords "Overweight", "Probiotics" and "Obesity", and published between 2012 and 2022. Results Six published studies met the inclusion criteria. The review showed that, although there is a lack of consensus in the literature, the use of probiotics in the absence of dieting produced a significant reduction in body weight and body mass index in 66.6% of the reviewed studies, a significant reduction in waist circumference in 80.0% of the reviewed studies, and an improvement in total body fat mass and waist circumference. Conclusions This review showed evidence of a trend in preventing body weight gain and reducing weight through the use of probiotics in individuals with excess weight or obesity. A combination of various strains of the genera Bifidobacterium and Lactobacillus was the most effective.